Role of Chemiluminescence examination as non-invasive diagnostic tool in early detection of Leukoplakia - Nidhi Jain; Anil Kumar Nagarajappa; Meenakshi Bhasin; Divya Pandya; Kaushal Pati Tripathi (Elsevier, 2018)
Objectives: To assess the efficacy of Chemiluminescent light (Vizilite plus) in enhancing visualization and its ability to highlight Leukoplakia lesion. Material and methods: This was a cross-sectional study done on 40 study subjects. Subjects were inducted into the study irrespective of age and sex based on the specific inclusion and exclusion criteria. The lesion parameters like the location of the lesion, the shape of lesion, the size, the extent, borders and the presence or absence of any adjacent satellite lesions were assessed under Incandescent light followed by Toluidine blue and Vizilite plus examinations. Histopathological examination results were considered as the gold standard and TBLU and CHEM outcomes were compared to them. Results: Vizilite plus examination method was most effective in assessing the size, borders and shape of the lesions followed by Toluidine blue and Incandescent light examinations. Toluidine blue and Vizilite plus examination methods demonstrated the sensitivity of 100% and specificity of 97.3%. They also demonstrated PPV of 100% and NPV of 75% with reliable accuracy of 97.5%. Conclusion: Chemiluminescent light is a stepping stone and has the potential to revolutionize the diagnostic protocol for patients with potentially premalignant lesions. The device can be used as a general oral mucosal examination system and may in particular improve the visualization of potentially premalignant lesions.